The relationship between changes in peak expiratory flow and asthma exacerbations in asthmatic children - Xiongbin Chen; Peng Han; Yan Kong; Kunling Shen (BMC, 2024)
Abstract Background Asthma is one of the most common chronic airway diseases in children. Preventing asthma exacerbation is one of the objectives of all asthma action plans. In patients with poor perception, it is difficult to identify acute asthma exacerbations by clinical asthma score, asthma control test or asthma control questionnaire. The aim of this study is to analyze whether children with asthma have changes in peak expiratory flow(PEF)before an acute asthma exacerbation and to evaluate the relationship between PEF and asthma exacerbation. Methods Basic information (including sex, age, atopy, etc.) and clinical information of asthmatic children who registered in the Electronic China Children's Asthma Action Plan (e-CCAAP) from 1 September 2017 to 31 August 2021 were collected. Subjects with 14 consecutive days of PEF measurements were eligible. Subjects in this study were divided into an exacerbation group and a control group. We analyzed the relationship between changes in PEF% pred and the presence of asthma symptoms. Result A total of 194 children with asthma who met the inclusion criteria were included, including 144 males (74.2%) and 50 females (25.8%), with a male-to-female ratio of 2.88:1. The mean age of the subjects was 9.51 ± 2.5 years. There were no significant differences in sex, age, allergy history or baseline PEF between the two groups. In children with and without a history of allergy, there was no significant difference between the variation in PEF at 14 days. Patients who only had a reduced in PEF but no symptoms of asthma exacerbation had the greatest reduction in PEF compared to the other groups. The most common cause of acute exacerbations of asthma is upper respiratory tract infection. Among the causes of acute exacerbations of asthma, the variation in PEF caused by air pollution was significantly higher than that of other causes (P < 0.05). In acute exacerbations, the decrease in PEF was significantly greater in the exacerbation group than in the control group. In children with asthma symptoms, there was a decrease in PEF approximately 1.34 days before the onset of symptoms. Conclusion Children with asthma show a decrease in PEF 1.34 days before the onset of asthma symptoms. We recommend that asthmatic children who show a decrease in PEF should step-up asthma therapy. The most common cause of acute exacerbations of asthma was upper respiratory tract infections, and the variation in PEF caused by air pollution was significantly higher than that caused by other factors.